Distribution Pattern of Shorea lepropsula Miq, Around the Forest Area With Special Purpose (KHDTK) Aek Nauli Indonesia - Latifah, Siti; Zahra, Ma'rifatin; Panggabean, Mario Dasiando (Jurnal Manajemen Hutan Tropika, 2023)
Shorea leprosula belongs to the Dipterocarpaceae family and grows in Indonesia's tropical forests which have an economic and ecological role. They are a plant in tropical forests that is known as a producer of fruit and tengkawang oil. The presence of S. leprosula trees in the habitat naturally at this time was very hard to find and began to decrease in population. This study aims to determine the potential and distribution pattern of S. leprosula found around KHDTK Aek Nauli. The research method uses the plot path method measuring 20 m × 20 m, the total number of plots is 150 plots. The research results show that the potency of S. leprosula is 63.17 m3 ha-1. The highest important value index of S. leprosula at the tree level was 25.45%. The distribution pattern of S. leprosula at the sapling, pole, and tree levels was clustered, while the distribution pattern at the seedling level was random. The importance of information about the potential and pattern of S. leprosula to be known as an indicator of the current status of its population at KHDTK Aek Nauli and as an information basis for managing management S. leprosula for support preservation in the forest.